Immigration policy and the Scandinavian welfare state 1945-2010 - Brochmann, Grete (Migration, diasporas and citizenship., 2012)
This book explores the historical development of post-war immigration politics in Norway, Sweden and Denmark from the perspective of the welfare state, examining how these welfare states with generous and inclusive welfare schemes and a strong sense of egalitarianism cope with the pressures of immigration and growing diversities. Through unique case studies and comparative historical analysis, the authors reveal significant differences between the strategies employed by the three countries to confront the challenge of immigration: Sweden as liberal, Denmark as restrictive and Norway somewhere in between, concluding that current patterns of divergence are consistent with earlier, more subtle variations.